Access barriers to justice. Community justice as an alternative in Peru (Società e diritti, 2019)
This essay is about access to law problems in Peru, taking up the hypothesis  that community justice might be an alternative to overcome those problems. The first section describes the three main obstacles or barriers confronting Peruvian citizens in obtaining hearings: economic, social and cultural barriers. In this context, an alternative is proposed in the form of community justice currently practiced by Aymara and Aguarunas communities and which, as we shall see, seems to be a viable option for the nation at large.Key words: Communal justice, access to justice, judicial reform, Alternative dispute resolution, Andean communities,Amazonian Community